2017
DOI: 10.5530/fra.2017.2.28
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anticancer Activities of Methanol Extract of Seeds of Datura stramonium l

Abstract: To carry out this Research work, plant materials viz., seeds of D. stramonium were collected from District Pulwama flanked by District Shopian of Jammu and Kashmir, India, lying at an latitude of 33̊ 72 N and a longitude of 74°53 E. It is situated in the laps of foot hills of Pir panjal Range, being a hilly terrain-it has an average elevation of 2057 meter. 7 The plant was authenticated by Prof. Dr. N. Raaman, Director, CAS in Botany, University of Madras, Chennai, India. Seeds were thoroughly washed and dried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…The ANOVA using the Dunnett Test showed that the antiradical activities of our bark extracts (p-value = 0.004 < 0.05) and leaves (p-value = 0.0001 < 0.05) are all lower than those of the positive controls tested: ascorbic acid with 3.05 ± 0.07 µg/ml, rutin with 2.79 ± 0.79 µg/ml and quercetin with 1.17 ± 0.03 µg/ml (Figure 4.). The high content of polyphenols and flavonoids (Figure 2) in the extracts would be responsible for the anti-free radical activities observed in our extracts; since a direct correlation between antioxidant activity and the reducing power of plant extracts involving phenolic compounds has been reported by many authors (Fatima et al, 2015;Iqbal et al, 2017;Togola et al, 2019;Fofié et al, 2017;Bagewadi et al, 2019). Other secondary metabolites (tannins, terpenes, sterols, etc.…”
Section: Discussionsupporting
confidence: 58%
“…The ANOVA using the Dunnett Test showed that the antiradical activities of our bark extracts (p-value = 0.004 < 0.05) and leaves (p-value = 0.0001 < 0.05) are all lower than those of the positive controls tested: ascorbic acid with 3.05 ± 0.07 µg/ml, rutin with 2.79 ± 0.79 µg/ml and quercetin with 1.17 ± 0.03 µg/ml (Figure 4.). The high content of polyphenols and flavonoids (Figure 2) in the extracts would be responsible for the anti-free radical activities observed in our extracts; since a direct correlation between antioxidant activity and the reducing power of plant extracts involving phenolic compounds has been reported by many authors (Fatima et al, 2015;Iqbal et al, 2017;Togola et al, 2019;Fofié et al, 2017;Bagewadi et al, 2019). Other secondary metabolites (tannins, terpenes, sterols, etc.…”
Section: Discussionsupporting
confidence: 58%
“…[4][5] The medicinal properties of traditional medicinal plants have been investigated in the recent scientific developments for treatment of many metabolic diseases. The extract of these plants from various places in the world are reported to possess several pharmacological activities including anti-inflammatory, [6][7] antidiabetic, [8][9][10][11] antimalarial, 12 antimicrobial, [13][14] anti TB, 15 anthelmintic activity, 16 anticancer, [17][18] cylindroxanthones A-C (1-3 etc. Traditional medicinal plants derived natural product such as alkaloids, flavonoids and terpenes.…”
Section: Introductionmentioning
confidence: 99%
“…The findings obtained are shown in Table 2. In previous studies, it was reported that petroleum ether, benzene, solvent ether, chloroform, acetone, ethanol and methanol extracts of D. stramonium had antioxidant potential with different methods (DPPH radical scavenging assay, Superoxide radical scavenging assay, ABTS + radical cation scavenging assay, Hydroxyl (OH) radical scavenging assay, Nitric oxide (NO) radical scavenging assay, Ferric (Fe3 +) reducing power assay, Phosphomolybdenum reduction assay) (Kumar et al, 2008;Sreenivasa et al, 2012;Iqbal et al , 2017;Belayneh et al, 2019). In our study, the antioxidant potential of EtoH extract of D. stramonium was determined for the first time using TAS and TOS kits.…”
Section: Antioxidant and Oxidant Statusmentioning
confidence: 99%